2008
DOI: 10.1021/ma8018014
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures in Thermosetting Blends of Epoxy Resin with Polydimethylsiloxane-block-poly(ε-caprolactone)-block-polystyrene ABC Triblock Copolymer

Abstract: Polydimethylsiloxane-block-poly(ε-caprolactone)-block-polystyrene ABC-type triblock copolymer (PDMS-b-PCL-b-PS) was synthesized via the sequential ring-opening polymerization and atom transfer radical polymerization. The ABC triblock copolymer was incorporated into epoxy to prepare the nanostructured thermosets. In terms of the difference in miscibility of epoxy with the subchains of the ABC triblock copolymer after and before curing reaction, it is proposed that the formation of the nanostructures follows the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 42 publications
7
76
0
Order By: Relevance
“…26,27 More recently, the demixing behavior of miscible blocks was also found in the nanostructured epoxy thermosets via reaction-induced microphase separation mechanism. 21,23 It is proposed that before curing reaction, all the subchains of block copolymers are miscible with the precursors of epoxy owing to the nonnegligible contribution of mixing entropy to mixing free energy. With the occurrence of curing reaction the subchains immiscible with epoxy are separated out to form the nanophases due to the decrease in mixing entropy (ΔS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 More recently, the demixing behavior of miscible blocks was also found in the nanostructured epoxy thermosets via reaction-induced microphase separation mechanism. 21,23 It is proposed that before curing reaction, all the subchains of block copolymers are miscible with the precursors of epoxy owing to the nonnegligible contribution of mixing entropy to mixing free energy. With the occurrence of curing reaction the subchains immiscible with epoxy are separated out to form the nanophases due to the decrease in mixing entropy (ΔS).…”
Section: Discussionmentioning
confidence: 99%
“…35,36,45 Rebizant et al 35,36 have reported the formation of the ordered nanostructures in epoxy thermosets containing polystyrene-block-polybutadiene-block-poly(methyl methacrylate) ABC triblock copolymers (PS-b-PB-b-PMMA). In the nanostructured thermosets PB blocks aggregates into spherical domains at the interface between the epoxy-rich matrix and spheres formed by the PS blocks.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that the energy-dissipation mechanisms could be related to the formation of shearing bands induced by the nanocavitation of PPO microdomains in the nanostructured epoxy thermosets containing ATPPO. [36,[51][52][53][54][55][56][57] …”
Section: Thermal and Mechanical Propertiesmentioning
confidence: 99%
“…In other systems, the epoxy prepolymer and the block copolymer can provide a homogeneous solution before curing, but during the curing process the nanostructure can form through a mechanism called reaction-induced microphase separation [9]. Some examples of the copolymers that give rise to nanoscopic structures include diblocks and/or triblocks of poly(ethylene oxide) with polycaprolactone (PEO-b-PCL) [9], poly(propylene oxide) (PEO-b-PPO) [10][11][12][13][14][15], poly(hexylene oxide) (PEO-b-PHO) [16], poly(n-butylene oxide) (PBO-b-PEO) [17], poly(ethyl ethylene) (PEO-b-PEE) [7,8], poly(ethylene-alt-propylene) (PEO-b-PEP) [7,8,[18][19][20][21], low molar mass polyethylene (PEO-b-PE) [22], polystyrene (PEO-b-PS) [23], and polydimethylsiloxane (PEO-b-PDMS) [24]; block copolymers of polycaprolactone with polydimethyl-siloxane (PCL-b-PDMS-b-PCL) [25,26], poly(n-butyl acrylate) (PCL-b-PBA) [27], polybutadiene(PCLb-PBD-b-PCL) [28], polystyrene (PCL-b-PS) [29], or poly(butadiene-co-acrylonitrile) (PCL-b-PBN-b-PCL) [30]; block copolymers of poly(methyl methacrylate) with polystyrene (PMMA-b-PS) [31,32], and ABC-type triblock copolymer composed of polystyrene-b-polybutadiene-b-poly(methyl methacrylate) (PS-b-PBD-b-PMMA) [33,34], and polydimethyl-siloxane-b-polycaprolactone-b-polystyrene (PDMS-b-PCL-b-PS) [35]. The formation of ordered nanostructures in these epoxy networks occurs because the PCL, PEO or PMMA block segments in these corresponding copolymers remain miscible with the epoxy matrix after curing, whereas the other immiscible block components separate out.…”
Section: Introductionmentioning
confidence: 99%